The Power of Norms: Gender Equality Reforms in the Parliaments of Fiji and Samoa - Kerryn Baker; Sonia Palmieri (Politics and Governance, 2024)
Parliaments are increasingly defined as “gendered institutions,” with rules, norms, and practices that are often stubbornly resistant to gender equality initiatives. The gender sensitive parliaments’ global agenda has made substantial progress in both drawing attention to the gendered nature of parliaments and in spearheading gender equality reform. While a positive trend, there remains a significant disconnect between the (global) normative framework that sets out this agenda and the realization of gender equality in national (local) parliaments. In this article, we build on previous work that begins to unpack and test the process of global norm localization through “contextualization” and “contestation.” We select new sites to test these processes—Fiji and Samoa—where specific gender equality reforms have been implemented in the past 10 years, one a gender mainstreaming mandate for parliamentary committees and the other a parliamentary gender quota. The Pacific Islands region presents an important cultural context worthy of exploration: Parliaments are not only overwhelmingly male-dominated, but many are also derivative of hegemonic masculinist cultures evident in the Westminster tradition, albeit hybridized with local political traditions. We compare and contrast the process by which these reforms were developed and implemented in each country and examine the extent to which they can be considered effective mechanisms for addressing gender inequalities. We find that the extent to which these reforms are sustainable and transformative depends on local contexts, local actors, and locally derived solutions. Specifically, the culturally relevant process of contesting the gender quota in Samoa constitutionally, electorally, and through the courts has localised and thereby legitimised this globally endorsed reform. By contrast, gender mainstreaming in Fiji’s parliamentary committees has been little more than a “tick-a-box” exercise, having had limited engagement from the political elite under a relatively autocratic regime.